Perancangan Sistem Informasi Akuntansi Kasir dan Laporan Keuangan Berbasis Web pada Warung Makan - Muhammad Rizki; Kiky Zulkifli (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to design a web-based cashier accounting and financial reporting information system at the Nasi Goreng Ngejoss Food Stall, which still uses manual recording. This study uses the SDLC waterfall model with stages of analysis, design, implementation, testing, and maintenance. Data were obtained through observation, interviews, and literature review. The system was designed using UML and implemented with PHP, CodeIgniter, and MySQL. The results show that the system is capable of automatically processing sales transactions, generating sales receipts, managing menu data, and displaying daily, monthly, and profit and loss reports in real time. The system implementation has been proven to improve the operational efficiency of the stall, reduce recording errors, and make it easier for the owner to monitor financial conditions.